Polyamide composition, extrusion molded product and tubular molded product
Patent Information
- Application Number
- JP2023126529
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-02
- Publication Date
- 2025-02-14
AI Technical Summary
【0009】 本発明によれば、難燃性、耐薬品性、柔軟性及び耐衝撃性のバランスに優れる成形体を得ることができるポリアミド組成物;並びに、当該ポリアミド組成物を含む、押出成形体及びチューブ状成形体を提供することができる。
Smart Images

Figure 2025022184000001 
Figure 2025022184000002 
Figure 2025022184000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyamide composition, an extrudate, and a tubular molded article. [Background technology]
[0002] Polyamide compositions are known to be used in various applications. For example, Patent Document 1 discloses a polyamide composition that can be used for wire protection tubes, etc. The polyamide composition disclosed in Patent Document 1 contains an impact modifier.
[0003] Patent Document 2 discloses a polyamide composition that can be used for automobile parts, etc. The polyamide composition disclosed in Patent Document 2 contains a specific polyamide, a specific modified resin, and at least one filler selected from a fibrous filler and a needle-like filler, and the filler is 5 to 50 parts by mass of the polyamide composition per 100 parts by mass of the total of the specific polyamide, the specific modified resin, and the filler. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-012771 A [Patent Document 2] JP 2008-179753 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, it has been known that polyamide compositions are used in cooling members that come into contact with refrigerants such as cooling water at high temperatures. Cooling members are required to have excellent properties such as chemical resistance, flexibility, and impact resistance as well as flame retardancy. However, as a result of the research of the present inventors, it has been found that the polyamide composition described in Patent Document 1 has room for improvement, for example, in terms of chemical resistance. In addition, it has been found that the polyamide composition described in Patent Document 2 has room for improvement, for example, in terms of flexibility. Although various polyamide compositions have been proposed in the prior art, it is not easy to obtain a polyamide composition that can give a molded product with an excellent balance of flame retardancy, chemical resistance, flexibility, and impact resistance.
[0006] Therefore, an object of the present invention is to provide a polyamide composition from which a molded article having an excellent balance of flame retardancy, chemical resistance, flexibility, and impact resistance can be obtained, and an extrusion molded article and a tubular molded article each containing the polyamide composition. [Means for solving the problem]
[0007] As a result of intensive research aimed at solving the above problems, the present inventors have conceived of the present invention described below and found that the problems can be solved. That is, the present invention is as follows.
[0008] [1] A polyamide composition comprising: a polyamide (A) having a terminal carboxyl group concentration [COOH] of less than 40 μeq. / g; an impact modifier (B); and a halogen-free flame retardant (C) having an average particle size (D50) of 10 μm or less, wherein, based on 100% by mass of the polyamide composition, the content of the polyamide (A) is 65% by mass or more, the content of the impact modifier (B) is 5 to 15% by mass, and the content of the halogen-free flame retardant (C) is 8 to 20% by mass; and further, the content of the filler (D) is 0% by mass or more and less than 4% by mass based on 100% by mass of the polyamide composition. [2] The polyamide composition according to [1], wherein the polyamide (A) is a polyamide containing diamine units (X) and dicarboxylic acid units (Y), the diamine units (X) contain diamine units (X1) derived from an aliphatic diamine having 4 to 18 carbon atoms, and the proportion of the diamine units (X1) is 10 to 50 mol % when the total of the diamine units (X) and the dicarboxylic acid units (Y) is 100 mol %. [3] The polyamide composition according to [2], wherein the diamine unit (X1) is at least one of a diamine unit derived from 1,9-nonanediamine and a diamine unit derived from 2-methyl-1,8-octanediamine. [4] The polyamide composition according to [2] or [3], wherein the dicarboxylic acid units (Y) contain dicarboxylic acid units (Y1) derived from an aromatic dicarboxylic acid, and the proportion of the dicarboxylic acid units (Y1) is 10 to 50 mol % when the total of the diamine units (X) and the dicarboxylic acid units (Y) is 100 mol %. [5] The polyamide composition according to [4], wherein the dicarboxylic acid unit (Y1) is a dicarboxylic acid unit derived from terephthalic acid. [6] The polyamide composition according to any one of [1] to [5], wherein the polyamide (A) has a melting point of 250 to 320°C. [7] The polyamide composition according to any one of [1] to [6], wherein the impact resistance improver (B) is an elastomer modified with at least one selected from the group consisting of carboxylic acids and derivatives thereof. [8] The polyamide composition according to any one of [1] to [7], wherein the halogen-free flame retardant (C) is a phosphinic acid compound. [9] The polyamide composition according to any one of [1] to [8], wherein the content of the halogen-free flame retardant (C) is 12 mass% or more, based on 100 mass% of the polyamide composition.
[10] The polyamide composition according to any one of [1] to [9], wherein a dumbbell-shaped tensile test piece (Type A1) made of the polyamide composition and described in JIS K 7139:2009 has a tensile strength measured at 23°C in accordance with ISO527-1:2019, and has a tensile strength retention of 79% or more before and after immersion in a cooling liquid at 130°C for 1,000 hours.
[11] The polyamide composition according to any one of [1] to
[10] , wherein a dumbbell-shaped tensile test piece (Type A1) made of the polyamide composition and described in JIS K 7139:2009 has a flexural modulus of 2.3 GPa or less, measured in accordance with ISO178:2010 at 23°C and a bending speed of 2 mm / min.
[12] An extrusion-molded article comprising the polyamide composition according to any one of [1] to
[11] .
[13] A tubular molded article comprising the polyamide composition according to any one of [1] to
[11] .
[14] The tubular molded article according to
[13] , which is selected from the group consisting of a wire protection tube, a battery coolant tube, and a motor coolant tube. Effect of the Invention
[0009] According to the present invention, it is possible to provide a polyamide composition which can give a molded article having an excellent balance of flame retardancy, chemical resistance, flexibility, and impact resistance; and an extrusion molded article and a tubular molded article which contain the polyamide composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention (hereinafter, sometimes referred to as "the present embodiment") will be described based on one example. However, the embodiment described below is an example for embodying the technical idea of the present invention, and the present invention is not limited to the following description. In addition, in this specification, preferred embodiments are shown, but a combination of two or more of the individual preferred embodiments is also a preferred embodiment. When there are several numerical ranges for matters shown as numerical ranges, the lower limit and upper limit can be selectively combined to form a preferred embodiment. In this specification, when a numerical range is stated as "XX to YY", it means "not less than XX and not more than YY". Furthermore, in this specification, a "unit" (where "" indicates a monomer) means a "structural unit derived from", for example, a "dicarboxylic acid unit" means a "structural unit derived from a dicarboxylic acid", and a "diamine unit" means a "structural unit derived from a diamine".
[0011] [Polyamide composition] The polyamide composition according to the present embodiment is a polyamide composition comprising a polyamide (A) having a terminal carboxy group concentration [COOH] of less than 40 μeq. / g, an impact modifier (B), and a halogen-free flame retardant (C) having an average particle size (D50) of 10 μm or less, wherein, based on 100% by mass of the polyamide composition, the content of the polyamide (A) is 65% by mass or more, the content of the impact modifier (B) is 5 to 15% by mass, and the content of the halogen-free flame retardant (C) is 8 to 20% by mass, and further, the content of the filler (D) is 0% by mass or more and less than 4% by mass based on 100% by mass of the polyamide composition.
[0012] The polyamide composition according to the present embodiment can provide a polyamide composition capable of giving a molded article having an excellent balance of flame retardancy, chemical resistance, flexibility, and impact resistance; and an extrusion molded article and a tubular molded article each containing the polyamide composition.
[0013] Usually, in a polyamide composition containing a flame retardant, when a certain amount of impact modifier is contained, the impact resistance can be improved in a wide temperature range, but the flame retardancy is relatively decreased. On the other hand, when the content of the halogen-free flame retardant is high, the content of the impact modifier is relatively low, and the number of flame retardant particles that can be the starting point of destruction increases, making it difficult to ensure impact resistance in a wide temperature range. Therefore, the content of the impact modifier and the content of the halogen-free flame retardant are usually in a trade-off relationship. In addition, when the contents of both the halogen-free flame retardant and the impact modifier are high, the content of the polyamide contained in the polyamide composition is relatively low. Therefore, the polyamide composition may not be able to fully exhibit heat resistance, mechanical strength, and chemical resistance. On the other hand, if a polyamide composition excellent in heat resistance, mechanical strength, and chemical resistance can be obtained, it can be used as a cooling member, etc., and it is expected that the versatility in applications in harsh environments can be improved. Furthermore, for example, in terms of improving the versatility in applications as a tubular member, it is preferable to increase the flexibility.
[0014] In contrast, the polyamide composition according to the present embodiment can provide a molded article having excellent balance of flame retardancy, chemical resistance, flexibility, and impact resistance. The reason is not limited to this theory, but is considered to be as follows. In the polyamide composition according to the present embodiment, by containing a predetermined amount of impact resistance improver (B) and a predetermined amount of halogen-free flame retardant (C) having an average particle size (D50) of 10 μm or less, this halogen-free flame retardant (C) is unlikely to become a fracture origin in the molded article. Furthermore, even if the content of the impact resistance improver (C) is 5 to 15 mass% relative to 100 mass% of the polyamide composition, it becomes possible to exhibit impact resistance in a wide temperature range. In the present embodiment, by using a polyamide having excellent chemical resistance, particularly a polyamide having excellent hydrolysis resistance, as the polyamide (A), it is possible to provide a molded article having even better chemical resistance.
[0015] Each component of the polyamide composition according to this embodiment will be described below.
[0016] <Polyamide (A)> The polyamide composition according to the present embodiment includes, as a polyamide, a polyamide (A) having a terminal carboxyl group concentration [COOH] of less than 40 μeq. / g. As long as the terminal carboxyl group concentration is less than 40 μeq. / g, the polyamide (A) may be one type or two or more types. Since the terminal carboxyl group concentration is less than 40 μeq. / g, the polyamide is less likely to decompose even under acidic conditions. This makes it possible to obtain a molded product having excellent chemical resistance, preferably excellent chemical resistance at high temperatures. In addition, since the polyamide (A) usually has properties such as excellent heat resistance and mechanical strength, such properties are also exhibited in the molded product.
[0017] The terminal carboxyl group concentration (unit: μeq. / g) refers to the amount of terminal carboxyl groups contained in 1 g of a compound (unit: μmol). The terminal carboxyl group concentration can be determined by preparing a sample solution and subjecting it to a neutralization titration method using potassium hydroxide. More specifically, the terminal carboxyl group concentration can be determined by the method described in the Examples.
[0018] From the viewpoint of improving chemical resistance, the terminal carboxyl group concentration [COOH] is preferably less than 35 μeq. / g, more preferably 30 μeq. / g or less, and even more preferably 25 μeq. / g or less. The lower limit of the terminal carboxyl group concentration [COOH] is not limited, but may be, for example, preferably 3 μeq. / g or more, more preferably 5 μeq. / g or more. The terminal carboxyl group concentration [COOH] can be adjusted by the ratio of the diamine and dicarboxylic acid, which are raw materials, and the amount of the terminal blocking agent added.
[0019] The polyamide (A) is preferably a polyamide comprising diamine units (X) and dicarboxylic acid units (Y).
[0020] Preferred embodiments of the diamine unit (X) and the dicarboxylic acid unit (Y) will be described later, but preferred examples of the polyamide (A) that become apparent from these preferred embodiments will be given first.
[0021] An example of a preferred polyamide (A) is a polyamide containing diamine units (X) and dicarboxylic acid units (Y), in which the diamine units (X) contain diamine units (X1) derived from an aliphatic diamine having 4 to 18 carbon atoms, and the proportion of the diamine units (X1) is 10 to 50 mol % when the total of the diamine units (X) and the dicarboxylic acid units (Y) is 100 mol %, and more preferably the diamine units (X1) are at least one of diamine units derived from 1,9-nonanediamine and diamine units derived from 2-methyl-1,8-octanediamine.
[0022] Another example of a preferable polyamide (A) is a polyamide containing diamine units (X) and dicarboxylic acid units (Y), wherein the dicarboxylic acid units (Y) contain dicarboxylic acid units (Y1) derived from an aromatic dicarboxylic acid, and the proportion of the dicarboxylic acid units (Y1) is 10 to 50 mol % when the total of the diamine units (X) and the dicarboxylic acid units (Y) is 100 mol %.
[0023] A more preferred example of the polyamide (A) is a polyamide containing diamine units (X) and dicarboxylic acid units (Y), in which the diamine units (X) contain diamine units (X1) derived from an aliphatic diamine having 4 to 18 carbon atoms, and the proportion of the diamine units (X1) is 10 to 50 mol % when the total of the diamine units (X) and the dicarboxylic acid units (Y) is taken as 100 mol %, and the dicarboxylic acid units (Y) contain dicarboxylic acid units (Y1) derived from an aromatic dicarboxylic acid, and the proportion of the dicarboxylic acid units (Y1) is 10 to 50 mol % when the total of the diamine units (X) and the dicarboxylic acid units (Y) is taken as 100 mol %, and more preferably the polyamide in which the dicarboxylic acid units (Y1) are dicarboxylic acid units derived from terephthalic acid.
[0024] (Diamine unit (X)) The diamine unit (X) preferably contains a structural unit derived from at least one selected from the group consisting of an aliphatic diamine, an alicyclic diamine, and an aromatic diamine, and more preferably contains a structural unit derived from an aliphatic diamine. Examples of the aliphatic diamine include one or more selected from linear aliphatic diamines and branched aliphatic diamines.
[0025] Examples of linear aliphatic diamines include ethylenediamine, 1,3-propanediamine, 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, 1,13-tridecanediamine, 1,14-tetradecanediamine, 1,15-pentadecanediamine, 1,16-hexadecanediamine, 1,17-heptadecanediamine, and 1,18-octadecanediamine.
[0026] Examples of branched aliphatic diamines include 1,2-propanediamine, 1-butyl-1,2-ethanediamine, 1,1-dimethyl-1,4-butanediamine, 1-ethyl-1,4-butanediamine, 1,2-dimethyl-1,4-butanediamine, 1,3-dimethyl-1,4-butanediamine, 1,4-dimethyl-1,4-butanediamine, 2-methyl-1,3-propanediamine, 2-methyl-1,4-butanediamine, 2-ethyl-1,4-butanediamine, and 2,3 -Dimethyl-1,4-butanediamine, 2-methyl-1,5-pentanediamine, 2-ethyl-1,5-pentanediamine, 2-propyl-1,5-pentanediamine, 3-methyl-1,5-pentanediamine, 2-butyl-2-ethyl-1,5-pentanediamine, 2,5-dimethyl-1,6-hexanediamine, 2,4-dimethyl-1,6-hexanediamine, 3,3-dimethyl-1,6-hexanediamine, 2,2-dimethyl-1,6-hexanediamine, 2,4 -Diethyl-1,6-hexanediamine, 2,2,4-trimethyl-1,6-hexanediamine, 2,4,4-trimethyl-1,6-hexanediamine, 2-ethyl-1,6-hexanediamine, 2-propyl-1,6-hexanediamine, 2-ethyl-1,7-heptanediamine, 2-propyl-1,7-heptanediamine, 2-methyl-1,8-octanediamine, 3-methyl-1,8-octanediamine, 1,3-dimethyl-1,8-octanediamine, 1,4- Dimethyl-1,8-octanediamine, 2,4-dimethyl-1,8-octanediamine, 3,4-dimethyl-1,8-octanediamine, 4,5-dimethyl-1,8-octanediamine, 2,2-dimethyl-1,8-octanediamine, 3,3-dimethyl-1,8-octanediamine, 4,4-dimethyl-1,8-octanediamine, 2-ethyl-1,8-octanediamine, 2-methyl-1,9-nonanediamine, and 5-methyl-1,9-nonanediamine.
[0027] Examples of the alicyclic diamine include cyclohexanediamine, methylcyclohexanediamine, norbornanedimethylamine, tricyclodecanedimethyldiamine, bis(4-amino-3-ethylcyclohexyl)methane, and bis(4-amino-3-ethyl-5-methylcyclohexyl)methane. Examples of aromatic diamines include p-phenylenediamine, m-phenylenediamine, p-xylylenediamine, m-xylylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfone, 4,4'-diaminodiphenylether, and 4,4'-methylenedi-2,6-diethylaniline.
[0028] The aliphatic diamine is preferably an aliphatic diamine having 4 to 18 carbon atoms. That is, the diamine unit (X) preferably contains a diamine unit (X1) derived from an aliphatic diamine having 4 to 18 carbon atoms. The aliphatic diamine is more preferably an aliphatic diamine having 4 to 12 carbon atoms, and further preferably an aliphatic diamine having 6 to 10 carbon atoms. This makes it easier for the polymerization reaction between the diamine and the dicarboxylic acid to proceed smoothly, and makes it easier to further improve the physical properties of the obtained polyamide.
[0029] In one embodiment of the present invention, the diamine unit (X) preferably contains a structural unit derived from at least one selected from the group consisting of 1,6-hexanediamine, 1,9-nonanediamine, 1,10-decanediamine, 2-methyl-1,5-pentanediamine, and 2-methyl-1,8-octanediamine, among the specific examples described above, more preferably contains a structural unit derived from at least one selected from the group consisting of 1,9-nonanediamine, 1,10-decanediamine, and 2-methyl-1,8-octanediamine, and even more preferably contains a structural unit derived from 1,9-nonanediamine and 2-methyl-1,8-octanediamine. That is, the diamine unit (X1) is preferably at least one of a diamine unit derived from 1,9-nonanediamine and a diamine unit derived from 2-methyl-1,8-octanediamine, and more preferably the diamine unit (X1) is composed of a diamine unit derived from 1,9-nonanediamine and a diamine unit derived from 2-methyl-1,8-octanediamine. The diamine unit (X) may be a structural unit derived from a single type of diamine, or may be a structural unit derived from two or more types of diamines.
[0030] In one embodiment of the present invention, from the viewpoint of making the effects of the present invention easier to be achieved, the content of the structural units derived from aliphatic diamine in the diamine unit (X) is preferably 60 to 100 mol %, more preferably 70 to 100 mol %, and even more preferably 80 to 100 mol %, based on 100 mol % of the total amount of structural units contained in the diamine unit (X). In one aspect of the present invention, the diamine units (X) contain diamine units (X1) derived from an aliphatic diamine having 4 to 18 carbon atoms, and from the viewpoint of making it easier to achieve the effects of the present invention, it is preferable that the proportion of the diamine units (X1) is 10 to 50 mol % when the total of the diamine units (X) and the dicarboxylic acid units (Y) is 100 mol %.
[0031] In one embodiment of the present invention, when the diamine unit (X) contains a constitutional unit derived from 1,9-nonanediamine and a constitutional unit derived from 2-methyl-1,8-octanediamine, the molar ratio of 1,9-nonanediamine to 2-methyl-1,8-octanediamine is preferably in the range of 95 / 5 to 40 / 60, more preferably in the range of 90 / 10 to 45 / 55, and even more preferably in the range of 90 / 10 to 50 / 50.
[0032] (Dicarboxylic acid unit (Y)) The dicarboxylic acid unit (Y) may include any dicarboxylic acid unit. The dicarboxylic acid unit (Y) preferably includes, for example, a structural unit derived from at least one selected from the group consisting of an aliphatic dicarboxylic acid, an aromatic dicarboxylic acid, and an alicyclic dicarboxylic acid. From the viewpoint of more easily achieving the effects of the present invention, the dicarboxylic acid unit (Y) more preferably includes a structural unit derived from at least one selected from the group consisting of an aromatic dicarboxylic acid and an alicyclic dicarboxylic acid, and further preferably includes a dicarboxylic acid unit derived from an aromatic dicarboxylic acid. That is, the dicarboxylic acid unit (Y) preferably includes a dicarboxylic acid unit (Y1) derived from an aromatic dicarboxylic acid.
[0033] Examples of aliphatic dicarboxylic acids include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedicarboxylic acid, dodecanedicarboxylic acid, dimethylmalonic acid, 2,2-diethylsuccinic acid, 2,2-dimethylglutaric acid, 2-methyladipic acid, and trimethyladipic acid.
[0034] Examples of aromatic dicarboxylic acids include terephthalic acid, isophthalic acid, diphenic acid, 4,4'-biphenyldicarboxylic acid, diphenylmethane-4,4'-dicarboxylic acid, diphenylsulfone-4,4'-dicarboxylic acid, 1,2-naphthalenedicarboxylic acid, 1,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 1,7-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 2,3-furandicarboxylic acid, 2,4-furandicarboxylic acid, 2,5-furandicarboxylic acid, and 3,4-furandicarboxylic acid.
[0035] Examples of the alicyclic dicarboxylic acid include 1,3-cyclopentanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, cycloheptanedicarboxylic acid, cyclooctanedicarboxylic acid, and cyclodecanedicarboxylic acid.
[0036] In one embodiment of the present invention, from the viewpoint of making the effects of the present invention easier to be exhibited, the dicarboxylic acid unit (Y) preferably contains a structural unit derived from at least one selected from the group consisting of terephthalic acid, cyclohexanedicarboxylic acid, and naphthalenedicarboxylic acid, more preferably contains a structural unit derived from at least one selected from the group consisting of terephthalic acid and naphthalenedicarboxylic acid, and further preferably contains a structural unit derived from terephthalic acid. That is, the dicarboxylic acid unit (Y1) is preferably a dicarboxylic acid unit derived from terephthalic acid. The dicarboxylic acid unit (Y) may be a structural unit derived from only one of the above dicarboxylic acids, or may be a structural unit derived from two or more dicarboxylic acids.
[0037] In one embodiment of the present invention, from the viewpoint of making the effects of the present invention easier to be achieved, the content of the constituent units derived from the aromatic carboxylic acid in the dicarboxylic acid unit (Y) is preferably 60 to 100 mol %, more preferably 70 to 100 mol %, and even more preferably 80 to 100 mol %, based on 100 mol % of the total amount of constituent units contained in the dicarboxylic acid unit (Y). In one embodiment of the present invention, from the viewpoint of making the effects of the present invention easier to be achieved, the total content of structural units derived from at least one selected from the group consisting of terephthalic acid and naphthalenedicarboxylic acid in the dicarboxylic acid unit (Y) is preferably 60 to 100 mol %, more preferably 70 to 100 mol %, and even more preferably 80 to 100 mol %, based on 100 mol % of the total amount of structural units contained in the dicarboxylic acid unit (Y). In one aspect of the present invention, the dicarboxylic acid units (Y) contain dicarboxylic acid units (Y1) derived from an aromatic dicarboxylic acid, and from the viewpoint of making the effects of the present invention easier to be achieved, it is preferable that the proportion of the dicarboxylic acid units (Y1) is 10 to 50 mol % when the total of the diamine units (X) and the dicarboxylic acid units (Y) is 100 mol %.
[0038] The molar ratio [(X) / (Y)] of the diamine unit (X) to the dicarboxylic acid unit (Y) in the polyamide (A) is preferably 45 / 55 to 55 / 45. When the molar ratio [(X) / (Y)] is within the above range, the polymerization reaction is likely to proceed smoothly, and a polyamide composition having desired excellent physical properties is likely to be obtained. The molar ratio of the diamine unit (X) to the dicarboxylic acid unit (Y) can be adjusted according to the compounding ratio (molar ratio) of the raw material diamine to the raw material dicarboxylic acid.
[0039] The total ratio of the diamine unit (X) and the dicarboxylic acid unit (Y) in the polyamide (A) (the ratio of the total number of moles of the diamine unit (X) and the dicarboxylic acid unit (Y) to the number of moles of all the constituent units constituting the polyamide (A)) is preferably 70 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, even more preferably 95 mol% or more, and may even be 100 mol%. The total ratio of the diamine unit (X) and the dicarboxylic acid unit (Y) in the polyamide (A) may be 100 mol% or less, 99.5 mol% or less, or 99.0 mol% or less. In one embodiment of the present invention, for example, the total ratio of the diamine unit (X) and the dicarboxylic acid unit (Y) in the polyamide (A) may be 70 to 100 mol%, 80 to 99.5 mol%, 90 to 99.5 mol%, or 95 to 99.0 mol%. When the total proportion of the diamine units (X) and the dicarboxylic acid units (Y) is within the above range, a polyamide composition having more excellent desired physical properties is easily obtained.
[0040] (amino carboxylic acid unit) The polyamide (A) may further contain aminocarboxylic acid units in addition to the diamine units (X) and the dicarboxylic acid units (Y). Examples of the aminocarboxylic acid unit include structural units derived from lactams such as caprolactam and lauryllactam; and aminocarboxylic acids such as 11-aminoundecanoic acid and 12-aminododecanoic acid. In one embodiment of the present invention, the content of the aminocarboxylic acid units in the polyamide (A) is preferably 0 to 30 molar parts, more preferably 0 to 20 molar parts, even more preferably 0 to 10 molar parts, and still more preferably 0 to 5 molar parts, relative to 100 molar parts in total of the diamine units (X) and dicarboxylic acid units (Y) constituting the polyamide (A).
[0041] (Trivalent or higher carboxylic acid unit) The polyamide (A) may contain, in addition to the diamine units (X) and dicarboxylic acid units (Y), structural units derived from trivalent or higher carboxylic acids such as trimellitic acid, trimesic acid, and pyromellitic acid, within a range that allows melt molding, so long as the effects of the present invention are not impaired.
[0042] (End capping agent unit) The polyamide (A) may contain structural units derived from a terminal capping agent (hereinafter also referred to as "terminal capping agent units"). When the polyamide (A) contains a terminal blocking agent unit, the content of the terminal blocking agent unit is preferably 1.0 to 10 molar parts, more preferably 2.0 to 5.0 molar parts, based on 100 molar parts of the diamine unit (X). When the content of the terminal blocking agent unit is within the above range, it is easy to obtain a polyamide (A) having the desired excellent physical properties. The content of the terminal blocking agent unit can be adjusted to be within the above desired range by appropriately adjusting the amount of the terminal blocking agent contained in the raw material. The content of the terminal blocking agent unit in the polyamide (A) can be determined, for example, by measuring the solution viscosity, calculating the total amount of terminal groups from the relational equation between the viscosity and the number average molecular weight, and then subtracting the amount of amino groups and the amount of carboxy groups determined by titration, as described in JP-A-7-228690; 1 For example, the method may be to use H-NMR to determine the amount of the diamine unit and the end-capping agent unit based on the integral values of the signals corresponding to the diamine unit and the end-capping agent unit. In the present invention, the latter method is preferred.
[0043] As the terminal blocking agent, a monofunctional compound having reactivity with a terminal amino group or a terminal carboxy group can be used.Specific examples include monocarboxylic acid, acid anhydride, monoisocyanate, monoacid halide, monoester, monoalcohol, monoamine, etc. From the viewpoint of reactivity and the stability of the blocked end, a monocarboxylic acid is preferable as a terminal blocking agent for a terminal amino group, and a monoamine is preferable as a terminal blocking agent for a terminal carboxy group.From the viewpoint of ease of handling, etc., a monocarboxylic acid is more preferable as a terminal blocking agent.
[0044] The monocarboxylic acid used as the terminal blocking agent is not particularly limited as long as it has reactivity with an amino group. For example, aliphatic monocarboxylic acids such as acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, pivalic acid, and isobutyric acid; alicyclic monocarboxylic acids such as cyclopentane carboxylic acid and cyclohexane carboxylic acid; aromatic monocarboxylic acids such as benzoic acid, toluic acid, α-naphthalene carboxylic acid, β-naphthalene carboxylic acid, methyl naphthalene carboxylic acid, and phenyl acetic acid; and any mixtures thereof. Among these, at least one selected from the group consisting of acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, and benzoic acid is preferred from the standpoint of reactivity, stability of blocked terminals, and price.
[0045] The monoamine used as the terminal blocking agent is not particularly limited as long as it has reactivity with a carboxyl group. For example, aliphatic monoamines such as methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, decylamine, stearylamine, dimethylamine, diethylamine, dipropylamine, dibutylamine, etc.; alicyclic monoamines such as cyclohexylamine, dicyclohexylamine, etc.; aromatic monoamines such as aniline, toluidine, diphenylamine, naphthylamine, etc.; and any mixtures thereof. Among these, at least one selected from the group consisting of butylamine, hexylamine, octylamine, decylamine, stearylamine, cyclohexylamine, and aniline is preferred from the viewpoints of reactivity, high boiling point, stability of blocked terminals, and price.
[0046] When the polyamide (A) contains a terminal blocking agent unit, the total proportion of the diamine units (X), dicarboxylic acid units (Y) and terminal blocking agent units in the polyamide (A) (the proportion of the total number of moles of the diamine units (X), dicarboxylic acid units (Y) and terminal blocking agent units to the number of moles of all structural units constituting the polyamide (A)) is preferably 70.5 to 100 mol%, more preferably 80 to 100 mol%, even more preferably 90 to 100 mol%, and still more preferably 95 to 100 mol%.
[0047] Specific examples of polyamide (A) include polynonamethylene sebacamide (polyamide 910), polynonamethylene dodecamide (polyamide 912), polydecamethylene sebacamide (polyamide 1010), polydecamethylene dodecamide (polyamide 1012), polydodecamethylene sebacamide (polyamide 1210), polydodecamethylene dodecamide (polyamide 1212), polyamide 10T / 11, polynonamethylene naphthalene dicarboxamide ( Polyamide 9N), polynonamethylene naphthalene dicarboxamide / poly(2-methyloctamethylene) naphthalene dicarboxamide copolymer (polyamide 9N / M8N), polynonamethylene terephthalamide (polyamide 9T), polynonamethylene terephthalamide / poly(2-methyloctamethylene) terephthalamide copolymer (polyamide 9T / M8T), polydecamethylene terephthalamide (polyamide 10T). Among these, it is preferable to use at least one selected from polynonamethylene naphthalene dicarboxamide / poly(2-methyloctamethylene) naphthalene dicarboxamide copolymer (polyamide 9N / M8N), polynonamethylene terephthalamide / poly(2-methyloctamethylene) terephthalamide copolymer (polyamide 9T / M8T), polyamide 10T, and polyamide 12T as the polyamide (A). In one example of this embodiment, the polyamide (A) is polynonamethylene terephthalamide / poly(2-methyloctamethylene) terephthalamide copolymer (polyamide 9T / M8T).
[0048] (Polyamide (A) content) The content of polyamide (A) is 65% by mass or more, as described above, when the polyamide composition is taken as 100% by mass. This allows the molded article to exhibit the excellent properties such as heat resistance and mechanical strength that polyamide (A) usually has. From the viewpoint of further enhancing such effects, the content of polyamide (A) is preferably 66% by mass or more, more preferably 67% by mass or more, and even more preferably 68% by mass or more. The content of polyamide (A) is preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less.
[0049] (Melting point of polyamide (A)) The melting point of the polyamide (A) is preferably 250 to 320° C. From the viewpoint of heat resistance, the melting point of the polyamide (A) is preferably 255° C. or higher, more preferably 260° C. or higher. From the viewpoint of moldability, the melting point of the polyamide (A) is preferably 315° C. or lower, more preferably 310° C. or lower. More specifically, the melting point of the polyamide (A) can be determined by the method described in the Examples.
[0050] (Intrinsic Viscosity of Polyamide (A)) The intrinsic viscosity of the polyamide (A) is preferably 0.5 dL / g or more, more preferably 0.7 dL / g or more. The intrinsic viscosity of the polyamide (A) is preferably 2.0 dL / g or less, more preferably 1.5 dL / g or less. The intrinsic viscosity of the polyamide (A) is preferably 0.5 to 2.0 dL / g. When the intrinsic viscosity is within the above range, it becomes easier to obtain a polyamide (A) having more excellent desired physical properties. The intrinsic viscosity of polyamide (A) can be determined by measuring the flow time of a solution in concentrated sulfuric acid having a concentration of 0.2 g / dL and a temperature of 30° C. More specifically, the intrinsic viscosity of polyamide (A) can be determined by the method described in the Examples.
[0051] The polyamide composition according to this embodiment may contain a polyamide (A') other than the polyamide (A). From the viewpoint of exerting the effects of the present invention well, it is preferable that the polyamide composition does not contain the polyamide (A'). The content of polyamide (A') in the polyamide composition is preferably 10 mass % or less, more preferably 5 mass % or less, even more preferably 1 mass % or less, and still more preferably 0 mass %.
[0052] (Production of Polyamide (A)) Polyamide (A) can be produced by any method known as a method for producing polyamide. For example, it can be produced by a melt polymerization method, a solid-state polymerization method, a melt extrusion polymerization method, etc., using dicarboxylic acid and diamine as raw materials. Among these, the solid-state polymerization method is preferable from the viewpoint of being able to better suppress thermal deterioration during polymerization.
[0053] For example, polyamide (A) is produced as a nylon salt by first adding diamine, dicarboxylic acid, and, if necessary, catalyst and end-capping agent all at once. At this time, the amount of terminal carboxyl groups can be easily controlled by adjusting the number of moles of all carboxyl groups and the number of moles of all amino groups contained in the reaction raw materials.
[0054] After the nylon salt is produced, it is heated and polymerized at a temperature of 200 to 250°C to form a prepolymer, which is then further polymerized in a solid phase or polymerized using a melt extruder. When the final stage of polymerization is carried out by solid phase polymerization, it is preferably carried out under reduced pressure or in an inert gas flow, and if the polymerization temperature is within the range of 200 to 280°C, the polymerization rate is high, productivity is excellent, and coloring and gelation can be effectively suppressed. When the final stage of polymerization is carried out using a melt extruder, the polymerization temperature is preferably 370°C or less, and when polymerization is carried out under such conditions, polyamide (A) is obtained that is almost free of decomposition and is less deteriorated.
[0055] Examples of catalysts that can be used in producing polyamide (A) include phosphoric acid, phosphorous acid, hypophosphorous acid, and salts or esters thereof. Examples of the salts or esters include salts of phosphoric acid, phosphorous acid, or hypophosphorous acid with metals such as potassium, sodium, magnesium, vanadium, calcium, zinc, cobalt, manganese, tin, tungsten, germanium, titanium, and antimony; ammonium salts of phosphoric acid, phosphorous acid, or hypophosphorous acid; ethyl esters, isopropyl esters, butyl esters, hexyl esters, isodecyl esters, octadecyl esters, decyl esters, stearyl esters, and phenyl esters of phosphoric acid, phosphorous acid, or hypophosphorous acid.
[0056] The amount of the catalyst is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, and even more preferably 0.03% by mass or more, relative to the total mass (100% by mass) of the raw materials, and is preferably 1.0% by mass or less, more preferably 0.8% by mass or less, and even more preferably 0.5% by mass or less. This allows the polymerization to proceed smoothly and makes it difficult for catalyst-derived impurities to be generated.
[0057] <Impact resistance improver (B)> The polyamide composition according to the present embodiment contains an impact modifier (B). The impact modifier (B) is preferably an elastomer modified with at least one selected from carboxylic acids and their derivatives (e.g., acid anhydride groups). The impact modifier (B) may be used alone or in combination of two or more.
[0058] Specific examples of unmodified elastomers before modification include olefin elastomers such as EPR (ethylene-propylene copolymer), EPDM (ethylene-propylene-diene copolymer), EBR (ethylene-butene copolymer), and EOR (ethylene-octene copolymer); styrene elastomers such as SBS (styrene-butylene-styrene block copolymer), SEBS (styrene-ethylene-butylene-styrene block copolymer), SEPS (styrene-ethylene-propylene-styrene block copolymer), and SIS (styrene-isoprene-styrene copolymer); α-olefin-(unsaturated carboxylic acid and / or unsaturated carboxylic acid ester) copolymers such as EEA (ethylene-ethyl acrylate copolymer), EMA (ethylene-methyl acrylate copolymer), EAA (ethylene-acrylic acid copolymer), and EMAA (ethylene-methyl methacrylate copolymer), and ionomers. The unmodified elastomers described above can be modified with at least one selected from carboxylic acids and their derivatives to obtain a modified elastomer. This can increase the compatibility with polyamide (A).
[0059] Among the modified elastomers described above, it is preferable to use an olefin-based elastomer having an ethylene-α-olefin copolymer as a basic skeleton, such as an ethylene-propylene copolymer, an ethylene-1-butene copolymer, or an ethylene-4-methyl-1-pentene copolymer, because the polyamide composition according to this embodiment, and in turn the extrusion molded article or tubular molded article formed therefrom, have better impact resistance and flexibility. In one aspect of this embodiment, a maleic anhydride-modified ethylene-butene copolymer is used as the impact modifier (B).
[0060] The content of the impact modifier (B) is 5 to 15 mass% as described above, when the polyamide composition is taken as 100 mass%. When the content is 5 mass% or more, the desired impact resistance can be ensured and the flexibility can be increased. From this viewpoint, the content of the impact modifier (B) is preferably 6 mass% or more, more preferably 7 mass% or more. When the content is 15 mass% or less, the content of the impact modifier (B) can be suppressed and the flame retardancy can be relatively increased. From this viewpoint, the content of the impact modifier (B) is preferably 14.5 mass% or less, more preferably 14 mass% or less.
[0061] <Halogen-free flame retardants (C)> The polyamide composition according to the present embodiment contains a halogen-free flame retardant (C) having an average particle size (D50) of 10 μm or less. As the halogen-free flame retardant (C), one kind may be used alone or two kinds may be used in combination, so long as the average particle size (D50) is 10 μm or less. By containing the halogen-free flame retardant (C), it is possible to improve the flame retardancy while reducing the environmental load.
[0062] The average particle size (D50) of the halogen-free flame retardant (C) can be determined by a method in accordance with JIS Z 8825:2022.
[0063] The halogen-free flame retardant (C) is not particularly limited as long as the average particle diameter (D50) is 10 μm or less, and a known flame retardant that does not contain a halogen element can be used. As the halogen-free flame retardant (C), a phosphorus-based flame retardant containing a phosphorus element can be preferably used, and more specifically, red phosphorus-based flame retardants, phosphoric acid ester-based flame retardants, phosphoric acid amide-based flame retardants, (poly)phosphate-based flame retardants, phosphazene-based flame retardants, phosphine-based flame retardants, etc. can be mentioned. Among these, phosphine-based flame retardants are preferred.
[0064] Examples of phosphine-based flame retardants include monophosphinates and diphosphinates (hereinafter, both may be collectively referred to as "phosphinates"). These may be used alone or in combination of two or more.
[0065] An example of the monophosphinate is a compound represented by the following general formula (1). [ka]
[0066] An example of the diphosphinate is a compound represented by the following general formula (2). [ka]
[0067] In the general formulas (1) and (2), R 1 , R 2 , R 3 and R 4 R each independently represents an alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, or an arylalkyl group having 7 to 20 carbon atoms. 5 represents an alkylene group having 1 to 10 carbon atoms, an arylene group having 6 to 10 carbon atoms, an alkylarylene group having 7 to 20 carbon atoms, or an arylalkylene group having 7 to 20 carbon atoms. M represents calcium, magnesium, aluminum, or zinc. m is 2 or 3, n is 1 or 3, and x is 1 or 2. In general formula (2), the value of 2×n and the value of the product of m and x are usually equal to each other.
[0068] The alkyl group may be a linear or branched saturated aliphatic group. The aryl group may be unsubstituted or substituted with various substituents, such as a phenyl group, a benzyl group, an o-toluyl group, or a 2,3-xylyl group.
[0069] The above-mentioned phosphinate can be produced in an aqueous solution using phosphinic acid and a metal component such as a metal carbonate, a metal hydroxide, or a metal oxide, as described in European Patent Application Publication No. 699708 and Japanese Patent Laid-Open No. 8-73720. These are usually monomeric compounds, but depending on the reaction conditions and the environment, they may contain polymeric phosphinates with a condensation degree of 1 to 3.
[0070] Examples of monophosphinic acids and diphosphinic acids that constitute the phosphinic acid salt include dimethylphosphinic acid, ethylmethylphosphinic acid, diethylphosphinic acid, methyl-n-propylphosphinic acid, methanedi(methylphosphinic acid), benzene-1,4-di(methylphosphinic acid), methylphenylphosphinic acid, and diphenylphosphinic acid.
[0071] Examples of the metal component constituting the phosphinate include calcium ions, magnesium ions, aluminum ions, and zinc ions.
[0072] Specific examples of the phosphinate include calcium dimethylphosphinate, magnesium dimethylphosphinate, aluminum dimethylphosphinate, zinc dimethylphosphinate, calcium ethylmethylphosphinate, magnesium ethylmethylphosphinate, aluminum ethylmethylphosphinate, zinc ethylmethylphosphinate, calcium diethylphosphinate, magnesium diethylphosphinate, aluminum diethylphosphinate, zinc diethylphosphinate, calcium methyl-n-propylphosphinate, magnesium methyl-n-propylphosphinate, aluminum methyl-n-propylphosphinate, zinc methyl-n-propylphosphinate, calcium methylenebis(methylphosphinate), and Examples of such compounds include magnesium methylene bis(methylphosphinate), aluminum methylene bis(methylphosphinate), zinc methylene bis(methylphosphinate), calcium phenylene-1,4-bis(methylphosphinate), magnesium phenylene-1,4-bis(methylphosphinate), aluminum phenylene-1,4-bis(methylphosphinate), zinc phenylene-1,4-bis(methylphosphinate), calcium methylphenylphosphinate, magnesium methylphenylphosphinate, aluminum methylphenylphosphinate, zinc methylphenylphosphinate, calcium diphenylphosphinate, magnesium diphenylphosphinate, aluminum diphenylphosphinate, and zinc diphenylphosphinate.
[0073] Among these, calcium dimethylphosphinate, aluminum dimethylphosphinate, zinc dimethylphosphinate, calcium ethylmethylphosphinate, aluminum ethylmethylphosphinate, zinc ethylmethylphosphinate, calcium diethylphosphinate, aluminum diethylphosphinate, and zinc diethylphosphinate are preferred from the viewpoints of the flame retardancy and electrical properties of the resulting polyamide composition and the availability of the phosphinate. One of these phosphinates may be used alone, or two or more of them may be used in combination.
[0074] As the phosphinate, in terms of the mechanical properties (toughness, rigidity, etc.) of the polyamide composition and the molded article made therefrom, as well as the appearance of the molded article, it is preferable to use a powder of the phosphinate that has been pulverized so that the average particle size of the phosphinate is 100 μm or less, and it is more preferable to use a powder that has been pulverized so that the average particle size is 50 μm or less.
[0075] The phosphinate does not necessarily have to be completely pure, and may contain unreacted substances or by-products as long as the effects of the present invention are not impaired.
[0076] The content of the halogen-free flame retardant (C) is 8 to 20% by mass, as described above, when the polyamide composition is taken as 100% by mass. The content is preferably 19% by mass or less, more preferably 18% by mass or less. This allows the molded article to fully exhibit the impact resistance and flexibility over a wide temperature range expected of the impact resistance improver (B). In addition, in this embodiment, the average particle size (D50) of the halogen-free flame retardant (C) is 10 μm or less, preferably less than 10 μm, so that the flame retardant is less likely to become a fracture origin in the molded article. Therefore, impact resistance over a wide temperature range can be ensured. From the viewpoint of flame retardancy, the content of the halogen-free flame retardant (C) is preferably 12% by mass or more, more preferably 16% by mass or more, when the polyamide composition is taken as 100% by mass.
[0077] The polyamide composition according to this embodiment may contain a halogen-free flame retardant (C') other than the halogen-free flame retardant (C). However, from the viewpoint of achieving the effects of the present invention satisfactorily, it is preferable that the polyamide composition does not contain the halogen-free flame retardant (C'). The content of the halogen-free flame retardant (C') in the polyamide composition is preferably 10 mass % or less, more preferably 5 mass % or less, even more preferably 1 mass % or less, and still more preferably 0 mass %.
[0078] <Filling material (D)> The polyamide composition according to this embodiment contains 0% by mass or more and less than 4% by mass of the filler (D) relative to 100% by mass of the polyamide composition. The content of the filler (D) is preferably 3% by mass or less, more preferably 2% by mass or less, and even more preferably 1% by mass or less. In one form of this embodiment, the polyamide composition contains 0% by mass of the filler (D). That is, it is preferable that the polyamide composition does not contain the filler (D). The filler (D) is a component that can be expected to improve mechanical strength but impairs flexibility. In this embodiment, it is possible to increase the versatility of the polyamide composition to applications where mechanical strength is sufficiently secured by the polyamide (A). The filler (D) excludes the above-mentioned halogen-free flame retardant (C) and flame retardants other than the halogen-free flame retardant (C).
[0079] Examples of the filler (D) include known inorganic fillers and organic fillers, except that the filler (D) does not include materials exemplified as other components (E) described below, such as antioxidants and colorants.
[0080] Examples of the filler (D) include glass fiber, glass flake, talc, kaolin, mica, silicon nitride, hydrotalcite, calcium carbonate, zinc carbonate, titanium oxide, calcium hydrogen phosphate, wollastonite, silica, zeolite, alumina, boehmite, aluminum hydroxide, calcium silicate, sodium aluminosilicate, magnesium silicate, ketjen black, acetylene black, furnace black, carbon nanotubes, graphite, graphene, brass, copper, silver, aluminum, nickel, iron, calcium fluoride, montmorillonite, expandable fluorine mica, apatite, fully aromatic polyamide fiber, boron fiber, liquid crystal polyester fiber, potassium titanate, aluminum borate, xonotlite, magnesium sulfate, zinc oxide, sepiolite, and graphite. These materials may be surface-treated with at least one selected from the group consisting of coupling agents and bundling agents. In the polyamide composition according to this embodiment, the total content of the above-mentioned filler (D) is 0% by mass or more and less than 4% by mass, relative to 100% by mass of the polyamide composition.
[0081] <Other ingredients (E)> The polyamide composition according to this embodiment may contain other components (E) as necessary in addition to the polyamide (A), the impact modifier (B), the halogen-free flame retardant (C) and the filler (D).
[0082] Examples of the other component (E) include antioxidants (E1) such as hindered phenol antioxidants, hindered amine antioxidants, phosphorus antioxidants, and thio antioxidants; colorants (E2) such as carbon black; stabilizers such as copper compounds; ultraviolet absorbers; light stabilizers; antistatic agents; flame retardant assistants; crystal nucleating agents; plasticizers; lubricants; glidants; dispersants; oxygen absorbers; and hydrogen sulfide adsorbents. In one aspect of this embodiment, the polyamide composition is a polyamide composition that does not contain a crystal nucleating agent.
[0083] The content of the other component (E) is not particularly limited as long as it does not impair the effects of the present invention, but is preferably 0.02 to 5 mass%, more preferably 0.03 to 4 mass%, and even more preferably 0.1 to 3 mass%, based on 100 mass% of the polyamide composition. In one aspect of the present embodiment, the polyamide composition does not contain a crystal nucleating agent. In another aspect of the present embodiment, the content of the colorant is preferably 5 mass% or less, more preferably 4 mass% or less, even more preferably less than 4 mass%, and even more preferably 3 mass% or less, based on 100 mass% of the polyamide composition.
[0084] The content of the impact resistance improver (B) is preferably 35 to 65 mass % from the viewpoint of the balance between impact resistance and flame retardancy, assuming that the total mass of the impact resistance improver (B) and the halogen-free flame retardant (C) is 100 mass %.
[0085] The content of the halogen-free flame retardant (C) is preferably 96 mass% or more, more preferably 97 mass% or more, and even more preferably 98 mass% or more, when the total mass of the halogen-free flame retardant (C) and the filler (D) is 100 mass%, and may be 100 mass%.
[0086] The total content of the filler (D) and the other components (E) is preferably 0.02-9 mass%, more preferably 0.03-8 mass%, and even more preferably 0.1-7 mass%, under the condition that the content of the filler (D) in the polyamide composition is less than 4 mass%, thereby making it possible to increase flexibility and suppress the impairment of the effects expected from the other components (component (A), component (B), and component (C)). The content of the other components (E) is preferably 96 mass% or more, more preferably 97 mass% or more, and even more preferably 98 mass% or more, when the total mass of the filler (D) and the other components (E) is taken as 100 mass%, and may be 100 mass%. In this case, it is preferable that the other components (E) include at least one selected from an antioxidant and a coloring material.
[0087] (Physical properties of polyamide composition) [Tensile strength retention rate] For a dumbbell-shaped tensile test piece (Type A1) described in JIS K 7139:2009 made of the polyamide composition according to the present embodiment, the tensile strength retention rate for the tensile strength measured at 23 ° C. in accordance with ISO527-1:2019 before and after immersion in a cooling liquid at 130 ° C. for 1000 hours is preferably 79% or more, more preferably 81% or more, and even more preferably 84% or more. Here, the tensile strength retention rate (%) is the ratio (percentage) of the tensile strength TS1 after immersion in the cooling liquid to the tensile strength TS0 before immersion in the cooling liquid. The molded article of the polyamide composition has excellent chemical resistance. By including a polyamide having a terminal carboxyl group concentration [COOH] of less than 40 μeq. / g as polyamide (A) in the polyamide composition, the chemical resistance tends to be improved.
[0088] [Flexural modulus] The dumbbell-shaped tensile test piece (type A1) described in JIS K 7139:2009 made of the polyamide composition according to the present embodiment has a flexural modulus of 2.3 GPa or less, more preferably 2.1 GPa or less, and even more preferably 1.9 GPa or less, measured at 23°C and a bending speed of 2 mm / min in accordance with ISO178:2010. Molded articles of the polyamide composition have excellent flexibility. By suppressing the content of the filler (D) in the polyamide composition to less than 4 mass%, flexibility tends to be improved.
[0089] [Charpy impact strength (23℃)] A notched rectangular specimen (dimensions: length x width x thickness = 80 mm x 10 mm x 4 mm) cut out from a dumbbell-shaped tensile test specimen (Type A1) described in JIS K 7139:2009 made of the polyamide composition according to this embodiment has a notched Charpy impact value of 19 kJ / m at 23°C measured in accordance with ISO179 / 1eA:2010. 2 It is preferable that the concentration is 22 kJ / m or more. 2 More preferably, 25 kJ / m or more. 2 The above is more preferable. A molded article of the polyamide composition has excellent impact resistance at room temperature. The impact resistance tends to be improved by increasing the content of the impact resistance improver (B) in the polyamide composition or by using a halogen-free flame retardant having an average particle size (D50) of 10 μm or less as the halogen-free flame retardant (C).
[0090] [Charpy impact strength (-40℃)] For a notched rectangular specimen (dimensions: length x width x thickness = 80 mm x 10 mm x 4 mm) made of the polyamide composition according to this embodiment, the notched Charpy impact value at -40°C measured in accordance with ISO179 / 1eA:2010 is 9 kJ / m 2 It is preferable that the concentration is 12 kJ / m or more. 2 More preferably, it is 15 kJ / m or more. 2More preferably, the above value is satisfied. A molded article of the polyamide composition has excellent impact resistance at low temperatures. Impact resistance tends to be improved by increasing the content of the impact resistance improver (B) in the polyamide composition or by using a halogen-free flame retardant having an average particle size (D50) of 10 μm or less as the halogen-free flame retardant (C).
[0091] [Flammability test results] It is preferable that a plate-shaped test piece having a thickness of 0.40 mm, a width of 12.5 mm, and a length of 125 mm made of the polyamide composition according to the present embodiment has a flame retardancy test result of V-2 or better in accordance with the UL94 standard. A molded article of the polyamide composition has excellent flame retardancy. In the polyamide composition, for example, by keeping the content of the impact resistance improver (B) within a predetermined amount and increasing the content of the halogen-free flame retardant (C), the flame retardancy tends to be improved.
[0092] [Molded body] The molded article according to the present embodiment includes the polyamide composition according to the present embodiment. An example of the molded article according to the present embodiment is an extrusion molded article. Another example of the molded article according to the present embodiment is a tubular molded article. The tubular molded article may be an extrusion molded article. The tubular molded article means a molded article having a hollow shape, and the cross section is not limited to a circular shape, but also includes a flat shape.
[0093] The molded article can be obtained by molding the polyamide composition according to the present embodiment by various molding methods such as injection molding, blow molding, extrusion molding, compression molding, stretch molding, vacuum molding, foam molding, etc. Furthermore, the molded article according to the present embodiment can also be obtained by composite molding of the polyamide composition according to the present embodiment and other polymers, etc.
[0094] [Examples of use] Examples of the molded article include gears, cams, various housings, water pumps, thermostat housings, valves, rollers, impellers, bearing retainers, spring holders, clutch parts, chain tensioners, tanks, wheels, connectors, switches, sensors, sockets, capacitors, hard disk parts, jacks, fuse holders, relays, coil bobbins, resistors, IC housings, LED reflectors, tubes around the engine, battery cooling tubes, motor cooling tubes, hydrogen tubes, server cooling tubes, wire protection tubes, wire coatings, and bus bar coatings.
[0095] As described above, the polyamide composition according to the present embodiment can provide a molded article having excellent balance of flame retardancy, chemical resistance, flexibility, and impact resistance. Therefore, even when used in an environment where it comes into contact with a coolant, which is preferably used as a cooling member for cooling purposes, it can maintain flame retardancy, chemical resistance, flexibility, and impact resistance. As a cooling member, it is preferable to use it as a tube around an engine, a battery cooling tube, a motor cooling tube, a hydrogen tube, a server cooling tube, an electric wire protection tube, an electric wire coating, and a bus bar coating. Examples of the tube around an engine include a battery coolant tube and a motor coolant tube.
[0096] Examples of the applications of the molded article are not limited to the above examples, and examples of molded articles for automobile applications include automobile interior and exterior parts, sliding parts, electrical parts, parts in the engine room, and cooling system parts. In addition, the polyamide composition according to this embodiment can be made into a molded article that requires heat resistance corresponding to electric and electronic parts and surface mounting processes. Such molded articles can be suitably used for surface mounting parts such as surface-mounted connectors, sockets, camera modules, power supply parts, switches, sensors, capacitor base plates, hard disk parts, relays, resistors, fuse holders, coil bobbins, and IC housings. EXAMPLES
[0097] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these.
[0098] The evaluations in the Production Examples, Examples and Comparative Examples were carried out according to the methods described below.
[0099] 1. Evaluation of polyamides related to the manufacturing examples 1-1. Intrinsic viscosity The prepolymers and polyamides obtained in the production examples described below were used as samples. The intrinsic viscosities ηinh (dL / g) of these samples were calculated using concentrated sulfuric acid as a solvent at a concentration of 0.2 g / dL and a temperature of 30° C. according to the following formula: ηinh=[ln(t1 / t0)] / c In the above formula, t0 represents the flow time (seconds) of the solvent (concentrated sulfuric acid), t1 represents the flow time (seconds) of the sample solution, and c represents the concentration (g / dL) of the sample in the sample solution (i.e., 0.2 g / dL).
[0100] 1-2.Melting point The melting points of the polyamides obtained in the Production Examples were measured using a differential scanning calorimeter "DSC7020" manufactured by Hitachi High-Tech Science Corporation. The melting point was measured in accordance with ISO11357-3 (2011, 2nd edition). Specifically, in a nitrogen atmosphere, a sample (polyamide) was heated from 30°C to 300°C at a rate of 10°C / min, and held at 300°C for 5 minutes to completely melt the sample, and then cooled to 50°C at a rate of 10°C / min and held at 50°C for 5 minutes. The peak temperature of the melting peak that appeared when the sample was heated again to 300°C at a rate of 10°C / min was taken as the melting point (°C). If there were multiple melting peaks, the peak temperature of the melting peak on the highest temperature side was taken as the melting point (°C).
[0101] 1-3. Terminal carboxyl group concentration [COOH] 0.5 g of the polyamide obtained in the Production Example was dissolved in 40 mL of orthocresol to prepare a sample solution. The obtained sample solution was titrated with a 0.01 N ethanolic potassium hydroxide solution using a potentiometric titration device manufactured by Kyoto Electronics Manufacturing Co., Ltd., and the terminal carboxyl group concentration [COOH] (unit: μeq. / g) of the polyamide was measured by detecting the inflection point of the potential.
[0102] 2. Evaluation of molded articles of polyamide compositions according to the examples and comparative examples 2-1.Chemical resistance (Preparation of dumbbell-shaped tensile test specimens) Using an injection molding machine (clamping force: 100 tons, screw diameter: φ32 mm) manufactured by Sumitomo Heavy Industries, Ltd., the polyamide compositions obtained in the examples and comparative examples were molded using a T-runner mold under conditions of a cylinder temperature 15 to 35°C higher than the melting point of the polyamide and a mold temperature of 140°C to produce dumbbell-shaped tensile test pieces (Type A1) described in JIS K 7139:2009.
[0103] (Coolant resistance at high temperatures) The above dumbbell-shaped tensile test pieces were subjected to a tensile test at 23°C in accordance with ISO527-1:2019 using an autograph (Instron universal testing machine (5969) and video extensometer), and the tensile strength TS0 before immersion in the chemical coolant was measured.
[0104] A chemical coolant was prepared by mixing "Toyota Genuine Super Long Life Coolant," an automobile engine coolant manufactured by Nippon Chemical Industry Co., Ltd., with water in a volume ratio of 50 / 50.
[0105] Next, the test piece for which the tensile strength TS0 was measured was immersed in the above-mentioned cooling liquid in a pressure-resistant container and left to stand for 1,000 hours in a thermostatic bath ("DE-303" manufactured by Mita Sangyo Co., Ltd.) set at 130°C. After 1,000 hours, the test piece was taken out and subjected to a tensile test in the same manner as above, and the tensile strength TS1 after immersion in the cooling liquid was measured.
[0106] The tensile strength retention rate (%) was then calculated using the following formula. Tensile strength retention rate (%) = (TS1 / TS0) x 100
[0107] 2-2.Flexibility (Measurement of bending modulus) The flexural modulus (GPa) of the dumbbell-shaped tensile test specimen (Type A1) prepared in 2-1 above was measured in accordance with ISO178:2010 using an autograph (Instron Corporation's "Universal Testing Machine (5969)" and a video extensometer) at 23°C, 50% RH, and a bending speed of 2 mm / min.
[0108] 2-3.Shock resistance A notched rectangular specimen (dimensions: length x width x thickness = 80 mm x 10 mm x 4 mm) was cut out from the dumbbell-shaped tensile specimen (Type A1) prepared in 2-1 above, and the notched Charpy impact value (kJ / m) was measured at 23°C (room temperature) and -40°C (low temperature) using a Charpy impact tester (Toyo Seiki Seisakusho "Digital Impact Tester DG-CB") in accordance with ISO179 / 1eA:2010. 2 ) was measured.
[0109] 2-4.Flame retardancy (Preparation of test pieces for flame retardancy evaluation) Using an injection molding machine "UH-1000" manufactured by Nissei Plastic Industrial Co., Ltd., the pellet-shaped polyamide compositions obtained in the Examples or Comparative Examples were injection molded under conditions of a cylinder temperature 15 to 35°C higher than the melting point of the polyamide and a mold temperature of 140°C, to produce plate-shaped test pieces A having a thickness of 0.40 mm, a width of 12.5 mm and a length of 125 mm, and plate-shaped test pieces B having a thickness of 0.75 mm, a width of 12.5 mm and a length of 125 mm.
[0110] (Flame retardancy testing in accordance with UL94 standards and evaluation of test results) The upper end of the plate-shaped test piece A was clamped to fix the test piece A vertically, and a specified flame (a blue flame with a height of 20±1 mm) was applied to the lower end for 10 seconds and then released, and the burning time of the test piece A (first time) was measured. Immediately after the fire was extinguished, the specified flame was applied to the lower end again for 10 seconds and then released, and the burning time of the test piece A (second time) was measured. The same measurement was repeated for five pieces, and a total of 10 data points were obtained, five for the first burning time and five for the second burning time. The total of the 10 data points was designated T, and the maximum value of the 10 data points was designated M, and the data points were evaluated according to the following evaluation criteria. Test piece B was also evaluated in the same manner.
[0111] [Evaluation Criteria] V-0: T was 50 seconds or less and M was 10 seconds or less, the flame did not rise to the clamp, and the flaming molten material did not fall and ignite the dry cotton set 12 inches below. V-1: T was less than 250 seconds and M was less than 30 seconds, and the other conditions were the same as V-0. V-2: T was less than 250 seconds and M was less than 30 seconds, the flame did not rise to the clamp, and the flaming molten material fell and ignited dry cotton set 12 inches below. Out of range: The result was inferior to the above evaluation standard "V-2".
[0112] The polyamides used in the examples and comparative examples were prepared as follows. <Production Example 1> (Preparation of Polyamide PA-1) The raw materials used were 9871.2 g (59.42 mol) of terephthalic acid, 9639.3 g (60.90 mol) of a 50 / 50 molar mixture of 1,9-nonanediamine and 2-methyl-1,8-octanediamine, 142.9 g (1.17 mol) of benzoic acid, and 9.8 g of sodium hypophosphite monohydrate (0.05% by mass relative to the total mass of the raw materials).
[0113] The raw materials and 5 liters of distilled water were placed in a 40-liter autoclave and replaced with nitrogen. The temperature inside the autoclave was raised to 220°C over 2 hours while stirring. At this time, the pressure inside the autoclave rose to 2MPa. After continuing the reaction for 2 hours, the temperature was raised to 230°C, and the temperature was kept at 230°C for another 2 hours, while the steam was gradually removed to keep the pressure at 2MPa. Next, the pressure was lowered to 1MPa over 30 minutes, and the reaction was continued for another hour. A prepolymer was obtained by removing the mixture from the autoclave. The intrinsic viscosity [ηinh] of this prepolymer was 0.2 dL / g.
[0114] The prepolymer was crushed to a particle size of 2 mm or less using a flake crusher manufactured by Hosokawa Micron Corporation. After drying at 100°C under reduced pressure for 12 hours, the prepolymer was subjected to solid-state polymerization at 230°C and 13 Pa (0.1 mmHg) for 10 hours to obtain polyamide PA-1. Polyamide PA-1 was white in color.
[0115] Based on the raw materials used, this polyamide PA-1 was estimated to contain terephthalic acid units and 1,9-nonanediamine units and 2-methyl-1,8-octanediamine units in a molar ratio of 50 / 50. The melting point of this polyamide PA-1 was 265°C, the intrinsic viscosity ηinh was 1.28 dL / g, and the terminal carboxyl group concentration ([COOH]) was 23 μeq. / g.
[0116] <Production Example 2> (Preparation of Polyamide PA-2) The raw materials used were 9871.2 g (59.42 mol) of terephthalic acid, 9544.3 g (60.30 mol) of a 50 / 50 molar mixture of 1,9-nonanediamine and 2-methyl-1,8-octanediamine, 142.9 g (1.17 mol) of benzoic acid, and 9.8 g of sodium hypophosphite monohydrate (0.05% by mass relative to the total mass of the raw materials).
[0117] The raw materials and 5 liters of distilled water were placed in a 40 liter autoclave and the atmosphere was replaced with nitrogen. Thereafter, polymerization was carried out in the same manner as in Production Example 1. The intrinsic viscosity [ηinh] of the prepolymer thus obtained was 0.2 dL / g.
[0118] The prepolymer was pulverized in the same manner as in Production Example 1, and then subjected to solid-phase polymerization in the same manner as in Production Example 1 to obtain polyamide PA-2. Polyamide PA-2 was white in color.
[0119] Based on the raw materials used, this polyamide PA-2 was estimated to contain terephthalic acid units and 1,9-nonanediamine units and 2-methyl-1,8-octanediamine units in a molar ratio of 50 / 50. The melting point of this polyamide PA-2 was 265°C, the intrinsic viscosity [ηinh] was 1.26 dL / g, and the terminal carboxyl group concentration ([COOH]) was 55 μeq. / g.
[0120] Polyamide compositions according to the examples and comparative examples were produced as follows.
[0121] <Example 1> (Production of polyamide composition) First, polyamide PA-1 as polyamide (A), impact modifier (B1) as impact modifier (B), flame retardant (C1) as halogen-free flame retardant (C), and antioxidant (E1) and colorant (E2) as other components (E) were fed to a co-rotating twin-screw extruder (Toshiba Machine Co., Ltd., "TEM-26SS") in the ratios shown in Table 1, melt-kneaded under shear conditions of φ36, L / D=46, screw speed of 150 rpm, discharge of 10 kg / hr, and cylinder temperature of 300°C, extruded into a strand, cooled, and cut to produce a pellet-shaped polyamide composition. The produced polyamide composition was subjected to various evaluations, and the results are shown in Table 1.
[0122] <Examples 2 to 4 and Comparative Examples 1, 3 to 6> A pellet-shaped polyamide composition was produced in the same manner as in Example 1, except that the types and amounts of each component were changed to those shown in Tables 1 and 2. The polyamide compositions thus produced were subjected to various evaluations, and the results are shown in Tables 1 and 2.
[0123] <Comparative Example 2> A pelletized polyamide composition was produced in the same manner as in Example 1, except that the types and amounts of each component were changed as shown in Table 2. However, the glass fiber (D1) as component (D) was fed from the side feed port of the co-rotating twin-screw extruder. In addition, various evaluations were carried out using the produced polyamide compositions. The results are shown in Table 2.
[0124] The components shown in Tables 1 and 2 are as follows. [Polyamide (A)] Polyamide PA-1: Polyamide of Production Example 1 [Polyamide (A')] Polyamide PA-2: Polyamide of Production Example 2
[0125] [Impact resistance improver (B)] Impact resistance improver (B1): Maleic anhydride modified ethylene-butene copolymer "TAFMER MH7010" manufactured by Mitsui Chemicals Inc. (acid anhydride content: 50 μmol / g)
[0126] [Halogen-free flame retardants (C)] Flame retardant (C1): Clariant Chemicals' "Exolit OP 930" (aluminum diethylphosphinate, average particle size (D50): less than 10 μm) [Halogen-free flame retardant (C')] Flame retardant (C2): Clariant Chemicals Co., Ltd. "Exolit OP 1230" (aluminum diethylphosphinate, average particle size (D50): 20-40 μm)
[0127] [Filler (D)] Glass fiber (D1): Owens Corning glass fiber "CS03JA-FT2A" (average fiber diameter: 3 μm, average fiber length: 0.5 μm)
[0128] [Other ingredients (E)] Antioxidant (E1): "SUMILIZER GA-80" manufactured by Sumitomo Chemical Co., Ltd. (3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane) Coloring material (E2): Mitsubishi Chemical carbon black "#980B")
[0129] Tables 1 and 2 show the compositions [mass %] of the polyamide compositions and the evaluation results of the molded articles of the examples and comparative examples. [Table 1] [Table 2]
[0130] As seen from Table 1, the molded articles of the polyamide compositions according to Examples 1 to 4 all had an excellent balance of flame retardancy, chemical resistance, flexibility, and impact resistance. As seen from Table 2, the molded articles of the polyamide compositions according to Comparative Examples 1 to 6 were inferior to the molded articles of the polyamide compositions according to Examples 1 to 4 in any one of the viewpoints of flame retardancy, chemical resistance, flexibility, and impact resistance.
[0131] Comparison between the Examples and Comparative Examples reveals that, in order to obtain a molded article having an excellent balance of flame retardancy, chemical resistance, flexibility and impact resistance, when a predetermined amount of impact resistance improver is contained in the polyamide composition, it is preferable to use, as the polyamide, a polyamide having a relatively low concentration of terminal carboxy groups, to use, as the halogen-free flame retardant, a flame retardant having a relatively small average particle size, to not use too much of the halogen-free flame retardant, and, if a filler is used, to keep its amount as small as possible.
[0132] The polyamide composition of the present invention is useful for various extrusion molded articles, particularly tubular molded articles (e.g., wire protection tubes, battery coolant tubes, and motor coolant tubes) that require a balance of flame retardancy, chemical resistance, flexibility, and impact resistance.
Claims
1. A polyamide composition comprising: a polyamide (A) having a terminal carboxyl group concentration [COOH] of less than 40 μeq. / g; an impact resistance improver (B); and a halogen-free flame retardant (C) having an average particle size (D50) of 10 μm or less, Relative to 100% by mass of the polyamide composition, The content of the polyamide (A) is 65% by mass or more, The content of the impact resistance improver (B) is 5 to 15 mass %, and The content of the halogen-free flame retardant (C) is 8 to 20 mass %, Furthermore, the polyamide composition, wherein the content of the filler (D) is 0 mass% or more and less than 4 mass% based on 100 mass% of the polyamide composition.
2. The polyamide (A) is a polyamide containing a diamine unit (X) and a dicarboxylic acid unit (Y), the diamine unit (X) contains a diamine unit (X1) derived from an aliphatic diamine having 4 to 18 carbon atoms, 2. The polyamide composition according to claim 1, wherein the proportion of the diamine units (X1) is 10 to 50 mol % when the sum of the diamine units (X) and the dicarboxylic acid units (Y) is 100 mol %.
3. The polyamide composition according to claim 2, wherein the diamine unit (X1) is at least one of a diamine unit derived from 1,9-nonanediamine and a diamine unit derived from 2-methyl-1,8-octanediamine.
4. The dicarboxylic acid unit (Y) includes a dicarboxylic acid unit (Y1) derived from an aromatic dicarboxylic acid, The polyamide composition according to claim 2 or 3, wherein the proportion of the dicarboxylic acid units (Y1) is 10 to 50 mol % when the total of the diamine units (X) and the dicarboxylic acid units (Y) is 100 mol %.
5. The polyamide composition according to claim 4, wherein the dicarboxylic acid unit (Y1) is a dicarboxylic acid unit derived from terephthalic acid.
6. The polyamide composition according to any one of claims 1 to 5, wherein the polyamide (A) has a melting point of 250 to 320°C.
7. The polyamide composition according to any one of claims 1 to 6, wherein the impact resistance improver (B) is an elastomer modified with at least one selected from the group consisting of carboxylic acids and derivatives thereof.
8. The polyamide composition according to any one of claims 1 to 7, wherein the halogen-free flame retardant (C) is a phosphinic acid compound.
9. The polyamide composition according to any one of claims 1 to 8, wherein the content of the halogen-free flame retardant (C) is 12 mass% or more relative to 100 mass% of the polyamide composition.
10. The polyamide composition according to any one of claims 1 to 9, wherein a dumbbell-shaped tensile test piece (Type A1) described in JIS K 7139:2009 made of the polyamide composition has a tensile strength measured at 23°C in accordance with ISO527-1:2019, and the tensile strength retention before and after immersion in a cooling liquid at 130°C for 1000 hours is 79% or more.
11. The polyamide composition according to any one of claims 1 to 10, wherein a dumbbell-shaped tensile test piece (Type A1) described in JIS K 7139:2009 made of the polyamide composition has a flexural modulus of 2.3 GPa or less, measured at 23°C and a bending speed of 2 mm / min in accordance with ISO178:2010.
12. An extruded article comprising the polyamide composition according to any one of claims 1 to 11.
13. A tubular molded article comprising the polyamide composition according to any one of claims 1 to 11.
14. 14. The tubular molding of claim 13, selected from the group consisting of wire protection tubing, battery coolant tubing, and motor coolant tubing.
Citation Information
Patent Citations
Polyamide resin composition and molded article comprising the same
JP2008179753A
Polyamide resin composition
JP2014012771A